2017
DOI: 10.1007/s11864-017-0463-3
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Incidence of Younger Patients With Colorectal Cancer: Questions About Screening, Biology, and Treatment

Abstract: Colorectal cancer (CRC) is the third leading cancer diagnosed globally and an important cause of cancer-related mortality. Of interest, while we have witnessed a declining incidence trend over the past few decades in the older population, incidence rates for adolescents and young adults have been increasing steadily. Several factors may well explain this apparent epidemic in the young, namely a lack of routine screening and emerging lifestyle issues such as obesity, lack of exercise, and dietary factors. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(151 citation statements)
references
References 156 publications
7
141
1
2
Order By: Relevance
“…This study also characterised the cohort in terms of clinicopathological features, which found locally advanced rectosigmoid disease to be typical of yCRC. Tumours were commonly located in the left side of the bowel, with a greater proportion of tumours (42.6%) occurring in the rectumconcurring with previous literature describing young-onset disease [7]. Although our cohort is relatively small, it includes all the patients in a geographical area, including both urban & rural populations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This study also characterised the cohort in terms of clinicopathological features, which found locally advanced rectosigmoid disease to be typical of yCRC. Tumours were commonly located in the left side of the bowel, with a greater proportion of tumours (42.6%) occurring in the rectumconcurring with previous literature describing young-onset disease [7]. Although our cohort is relatively small, it includes all the patients in a geographical area, including both urban & rural populations.…”
Section: Discussionmentioning
confidence: 81%
“…CRC is the third most common cancer worldwide, with approximately 10% of cases affecting patients aged under 55 years [4,6]. These younger patients often present with more advanced disease and adverse pathological features compared to their older counterparts [7]. This may have a negative impact on their survival outcome [8].…”
Section: Introductionmentioning
confidence: 99%
“…With the emerging evidence that sporadic, young-onset CRC may have distinct molecular features compared to cancers that arise in older individuals (e.g. chromosomal instability, higher prevalence of mucinous or poorly differentiated tumors), 2226 and the fact that these patients are often detected at a more advanced stage 9 with dramatically greater years of life lost, 27 there is an urgent and unmet public health and clinical need to identify risk factors of young-onset CRC to develop targeted preventive and detection strategies for younger adults with higher risk. 8,28 …”
Section: Introductionmentioning
confidence: 99%
“…With the advent of colonoscopy and other screening modalities, an overall declining trend of CRC has been observed, particularly in older populations. 1 However, for unclear reasons, a rise in CRC incidence has been reported in patients aged < 50 years. [1][2][3] Younger patients tend to present with more advanced disease, which may reflect different tumor biology.…”
Section: Introductionmentioning
confidence: 99%